Working conditions of social workers graduates from Universidad Mariana in Pasto-Colombia. Between job insecurity and the impact on professional practice - Lasso-Urbano, Carlos; Moncayo-Quiñonez, Silvia Berenice Rocío; Coral-Domínguez, Ana Lucía (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
The article reveals the working conditions of social workers, who graduated from the Mariana University of Pasto, Colombia, between 2015-2020 working in the municipalities of Pasto, Tumaco, and Ipiales, department of Nariño. The research was developed from a mixed paradigm: qualitative and quantitative, through the application of a survey and semi-structured interviews with professionals from the region on which the study was focused. The various circumstances they face in the framework of their professional practice were identified: outsourcing, low wages, and long working hours, as well as the impact on their mental health caused by the prevailing job insecurity. It was concluded that it is urgent to implement the professional association of social workers in the department of Nariño to demand decent working conditions, and fair wages and to denounce the facts of precarization and labor flexibility present in public, private, and third-sector institutions.